Immersive virtual reality in experiential learning for architecture design education: an action research - Ummihusna, Annisa; Zairul, Mohd; Ab Jalil, Habibah; Sulaiman, Puteri Suhaiza (Emerald Publishing, 2024)
Purpose: Challenges of conducting site visit activities, a vital component of architecture learning during the recent pandemic have proved our unreadiness in facing the digital future. The lack of understanding of learning technology has affected the education experience. Thus, there is a need to investigate immersive learning technology such as immersive virtual reality (IVR) to replace students’ concrete experience in the current learning setting. This study aims to answer: (1) What is the influence of IVR in experiential learning (EL) in enhancing the personal spatial experience? (2) Does IVR in EL influence students' approach to learning during the architecture design process? Design/methodology/approach: The research was conducted as an action research design approach. Action research was employed in the first-year architecture design studio by the lecturer as a practitioner-researcher. The personal spatial experience survey was performed in the earlier phase to identify the students’ prior spatial experience. Architectural Spatial Experience Simulation (ASES) a learning tool was implemented and assessed with Architecture Design Learning Assessment (ADLA) rubric, which was developed to evaluate EL and student’s approach to learning during the architecture design learning process. Findings: The outcomes revealed that ASES as a learning tool in EL could improve the participants’ spatial experience, particularly those with minimal prior personal spatial experience. ASES was recognized to enhance the participants’ EL experience and encourage changes in student’s approach to learning from surface to deep learning. Originality/value: This research benefits the architecture design learning process by offering a learning tool and a framework to resolve challenges in performing site visit activities and digital learning. It also contributes by expanding the EL theory and students’ approach to learning knowledge in the architecture education field. © 2024, Emerald Publishing Limited.